Method for improving compactness of aluminum bronze extruded bar

Through the introduction of inert gases and large extrusion ratio in the melting and extrusion process of aluminum and bronze, the problem of loose and pinhole defects in aluminum bronze squeezed rods was solved, and its density and material performance were significantly improved.

CN119372506APending Publication Date: 2025-01-28CHINALCO LUOYANG COPPER PROCESSING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411493001.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-28

Smart Images

  • Figure CN119372506A_ABST
    Figure CN119372506A_ABST
Patent Text Reader

Abstract

The invention provides a method for improving compactness of an aluminum bronze extruded bar. The method mainly comprises the steps of casting, saw cutting, extruding, head cutting and tail removing, acid pickling and flaw detection. The casting method specifically comprises the following steps: firstly, proportioning according to the proportioning requirement, and putting dry raw materials into an electric induction furnace to be melted into a melt; when the temperature of the melt reaches 1140-1260 DEG C, inert gas is introduced into the melt from the bottom of the electric induction furnace, the pressure of the introduced inert gas at least can enable an oxidation film on the top of the melt to be broken, and the gas introduction time is not shorter than 20 min; and sampling and analyzing, adjusting components, refining, filtering, and casting to obtain a round ingot blank. By improving the casting and extruding steps, the prepared aluminum bronze extruded bar is excellent in internal structure, free of loose and pinhole defects, qualified in flaw detection and high in compactness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum bronze preparation, in particular to a method for improving the compactness of aluminum bronze extruded rods. Background Art

[0002] Extruded aluminum bronze bars are widely used in manufacturing various mechanical structural parts with harsh use conditions due to their high strength, hardness, good corrosion resistance, wear resistance and heat resistance. They are also used in the JG and GF fields, which have extremely strict requirements on the internal quality of the material.

[0003] Porosity and pinholes in extruded aluminum bronze bars are common quality defects, which mainly come from the residual porosity and pinhole defects in the ingot used in extruding the bars. This defect is very small and difficult to detect, which not only deteriorates the material properties, but sometimes causes serious material failure accidents. Therefore, it is particularly important to improve the density of extruded aluminum bronze bars.

[0004] At present, conventional melting and casting equipment used in the production of aluminum bronze ingots includes cored induction furnaces and coreless induction furnaces. The melting process is generally carried out in two ways: flux-covered and uncovered. Under normal circumstances, when melting in a furnace with a large capacity (more than 1 ton), regardless of whether there is a covering agent above the melt, according to the traditional oxidation degassing process, the gas in the melt is not easy to be completely discharged, resulting in more or less loose or pinhole defects inside the melt after it is cast into an ingot. Some loose defects of the ingot will be bridged during the extrusion process, and the density of the rod will be improved to a certain extent; some loose and pinhole defects cannot be eliminated after extrusion, and remain in the rod, affecting the density of the rod.

[0005] The looseness or pinhole defects of extruded aluminum bronze bars are an industry technical problem encountered by copper processing companies. Therefore, it is necessary to develop a preparation method to eliminate the internal pores of aluminum bronze extruded bars and improve their density. Summary of the invention

[0006] In order to solve the deficiencies in the prior art, the present invention provides a method for improving the density of aluminum bronze extruded rods. The present invention improves the melting and extrusion steps so that the prepared aluminum bronze extruded rods have excellent internal structure, no loose pinhole defects, qualified flaw detection, and high density.

[0007] In order to achieve the above object, the specific scheme adopted by the present invention is: A method for improving the compactness of aluminum bronze extruded rods, comprising the steps of melting, sawing, extruding, trimming, pickling and flaw detection; Among them, the specific method of melting and casting is: (1) Mix the ingredients according to the ratio requirements and put the dried raw materials into an induction furnace to melt them into a melt; (2) When the melt temperature reaches 1140-1260°C, inert gas is introduced into the melt from the bottom of the induction furnace. The pressure of the inert gas should at least be enough to rupture the oxide film on the top of the melt, and the ventilation time should not be less than 20 minutes. (3) Take samples for analysis, adjust the composition, refine, filter, and cast round ingots.

[0008] Furthermore, after the round ingot is sawn into an ingot of a length specified by the process, the ingot is heated to 740-900°C and then fed into an extrusion barrel of an extruder for extrusion to obtain an extruded rod of the required specification; Among them, the preheating temperature of the extrusion die and the extrusion pad is 300-400°C; the preheating temperature of the extrusion barrel is 380-450°C, the extrusion speed is 12-20 mm / s, and the extrusion ratio is ≥15.

[0009] Furthermore, when the extruded rod is trimmed and the head and tail are trimmed, 300-500 mm of the tail is trimmed and 100-200 mm of the head is trimmed.

[0010] Furthermore, the aluminum content in the aluminum bronze extruded rod is not less than 5%.

[0011] Beneficial effects:

[0012] Slag formation is serious during the aluminum bronze smelting process. When the induction furnace is smelted, the furnace lining becomes thicker and thicker, the power becomes smaller, and the stirring capacity of the furnace also becomes weaker. Even if the stirring force of the furnace is taken into consideration when the equipment is introduced, as production progresses or the equipment ages, the stirring capacity often fails to meet the conditions required for oxidation degassing. The present invention introduces inert gas to increase the stirring capacity of the melt. Regardless of the condition of the equipment itself, it can ensure that the melt can be thoroughly degassed, thereby solving the problem of unstable quality of loose pinholes in ingots often encountered in aluminum bronze casting production, and basically eliminating the defects of extruded aluminum bronze bars from the root. At the same time, the use of a large extrusion ratio process improves the internal quality and density of the bars, especially providing quality assurance for aluminum bronze materials with important uses. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is the microstructure diagram of the ingot in Example 3.

[0014] Figure 2 This is the microstructure diagram of the ingot in Comparative Example 6.

[0015] Figure 3 This is a high-magnification microstructure diagram of the rod produced in Example 3.

[0016] Figure 4 This is a high-magnification microstructure diagram of the rod produced in Comparative Example 2. DETAILED DESCRIPTION

[0017] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0018] The invention provides a method for improving the compactness of aluminum bronze extruded rods, which is suitable for producing aluminum bronze ingots in an induction furnace and extruding aluminum bronze rods on an extruder with a tonnage of more than 20MN.

[0019] 1. About the densification method of aluminum bronze ingot

[0020] There are two types of pores in copper alloys: hydrogen pores and water pores. For aluminum bronze, aluminum bronze contains more than 5% aluminum. Because the aluminum in copper has a high solubility in hydrogen, the main matrix after solidification is mainly copper, which has a low solubility in hydrogen, resulting in hydrogen pores in the ingot.

[0021] Aluminum is an element with stronger reactivity than copper. During normal smelting, aluminum forms a thin oxide film after oxidation, which reduces the oxidation of other elements in the copper liquid. According to the law of hydrogen and oxygen dissolution in copper, one of the commonly used measures to remove hydrogen from copper and copper melt is oxidation. Therefore, the oxide film on the surface of the copper liquid is broken, and the copper liquid is fully oxidized, and the hydrogen in the melt can be completely removed.

[0022] It has been found in practice that when the aluminum bronze solid material in the furnace melts and reaches a certain temperature, nitrogen or other inert gases are introduced into the melt through a gas pipe or bottom blowing brick to fully stir the melt and break the oxide film on the surface of the copper liquid. The copper liquid reacts with oxygen in the air, reducing the solubility of hydrogen in the melt, and it continuously escapes with the inert gas floating up, thereby greatly reducing the hydrogen content in the copper liquid, and the ingot structure is dense, without obvious loose pinhole defects.

[0023] 2. Densification methods for large extrusion ratio processes

[0024] Aluminum bronze extruded rods are processed by a suitable extrusion process. After the ingot is hot extruded, the tiny loose pinholes remaining from the casting are pressed together, the casting structure is transformed into the processed structure, and the density of the structure is further improved. The extrusion ratio of the aluminum bronze rod should be above 7 in principle. The higher the extrusion ratio, the more complete the deformation, and the better the effect of improving the density of the structure. In order to achieve the best high-density preparation effect, the present invention determines the minimum extrusion ratio in the preparation process method to be 15, thereby further improving the density of the rod.

[0025] Example 1

[0026] The present invention provides a method for improving the compactness of aluminum bronze extruded rods, the method comprising the following steps: S1. Put the raw materials for producing aluminum bronze QAl10-3-1.5 into a 2.5-ton induction furnace for melting, and completely melt them to a temperature of 1150°C; S2. Insert the gas pipe connected to the gas into the copper liquid in the furnace, as close to the bottom as possible; open the inert gas valve on the gas pipe; or open the gas valve of the bottom-blown brick under the furnace to introduce inert gas into the furnace; adjust the pressure of the inert gas to 3KPa, and the oxide film of the upper melt in the furnace breaks; continue ventilation for 30 minutes; S3. After the ventilation is completed, the valve is closed, and other normal melting and casting operations such as component analysis and adjustment are carried out, and then a φ195mm aluminum bronze round ingot is semi-continuously cast; S4, sawing the φ195mm aluminum bronze round ingot into φ195×400mm ingots; S5, heating the ingot obtained in step S4 and feeding it into the extrusion barrel of the hot extruder, and extruding it into a rod with a specification of φ38 mm; the heating temperature of the ingot during extrusion is 740°C, the extrusion speed is 20 mm / s; the preheating temperature of the extrusion die and the extrusion pad is 300°C; the preheating temperature of the extrusion barrel is 380°C; the extrusion ratio is set to 27.3; S6. Cut off 300-500mm of the tail of the φ38mm extruded bar and 100-200mm of the head, then pickle the bar to remove the oxide scale; S7. Ultrasonic flaw detection of the bar after the oxide scale is removed; S8. The bars obtained in step S7 are subjected to mechanical property testing, appearance and size inspection, and are cut to size, packaged and stored after they pass the inspection.

[0027] The following examples and comparative examples are described based on Example 1. Depending on the production brand and specifications, the melting temperature, casting parameters, ingot extrusion heating temperature, etc. may be slightly different from those in the above-mentioned examples, which are described below.

[0028] Firstly, on the same 2.5 ton coreless induction furnace, the common aluminum bronze round ingots containing other elements (such as iron, nickel, manganese, etc.) in addition to aluminum are produced, and the raw materials used are all geometric wastes returned from processing and casting.

[0029] Secondly, different aluminum bronzes are smelted at different melting temperatures. The melting temperature of aluminum bronze containing nickel element can be about 50°C higher than that of QAl10-3-1.5 in the above embodiment.

[0030] The pressure of the inert gas can be adjusted according to the capacity of the furnace. In the embodiment, a 2.5-ton melting furnace is used. When the pressure reaches 2.5 KPa, the oxide film of the upper melt in the furnace is broken.

[0031] According to the capacity of the furnace, for furnaces with a capacity of more than one ton, the ventilation time should not be less than 20 minutes; after the ventilation is completed, the valve is closed and other normal melting and casting operations are carried out to semi-continuously cast φ195mm oblong ingots.

[0032] Example 2

[0033] The difference from Example 1 is that: (1) in step S2, the pressure of the inert gas is adjusted to 2.5 KPa, and the oxide film of the melt above the furnace is broken; ventilation is continued for 25 minutes; (2) in step S5, the ingot obtained in step S4 is heated and sent to the extrusion barrel of the hot extruder to be extruded into a rod with a specification of φ50 mm; the ingot heating temperature during extrusion is 800°C, and the extrusion speed is 18 mm / s; the preheating temperature of the extrusion die and extrusion pad is 350°C; the preheating temperature of the extrusion barrel is 380°C; and the extrusion ratio is set to 15.76.

[0034] Example 3

[0035] The difference from Example 1 is that: (1) the raw materials for producing aluminum bronze QA19-2 are put into a 2.5-ton induction furnace for melting, completely melted and the temperature reaches about 1250°C; (2) in step S2, the pressure of the inert gas is adjusted to 3KPa, and the oxide film of the melt above the furnace is broken; ventilation is continued for 20 minutes; (3) in step S5, the ingot obtained in step S4 is heated and sent to the extrusion barrel of the hot extruder to be extruded into a rod with a specification of φ40mm; the ingot heating temperature during extrusion is 780°C, and the extrusion speed is 15mm / s; the extrusion die and extrusion pad are preheated to 400°C; the extrusion barrel is preheated to 420°C; and the extrusion ratio is set to 24.63.

[0036] Example 4

[0037] The difference from Example 3 is that: (1) in step S2, the pressure of the inert gas is adjusted to 2.5 KPa, and the oxide film of the melt above the furnace is broken; ventilation is continued for 20 minutes; (3) in step S5, the ingot obtained in step S4 is heated and sent to the extrusion barrel of the hot extruder to be extruded into a rod with a specification of φ30 mm; the ingot heating temperature during extrusion is 760°C, and the extrusion speed is 16 mm / s; the preheating temperature of the extrusion die and extrusion pad is 350°C; the preheating temperature of the extrusion barrel is 400°C; and the extrusion ratio is set to 43.78.

[0038] Example 5

[0039] The difference from Example 1 is that: (1) the raw materials for producing aluminum bronze QA19-4 are put into a 2.5-ton induction furnace for melting, completely melted and the temperature reaches about 1200°C; (2) in step S2, the pressure of the inert gas is adjusted to 3.5 KPa, and the oxide film of the melt above the furnace is broken; ventilation is continued for 23 minutes; (3) in step S5, the ingot obtained in step S4 is heated and sent to the extrusion barrel of the hot extruder to be extruded into a rod with a specification of φ38 mm; the ingot heating temperature during extrusion is 840°C, and the extrusion speed is 15 mm / s; the preheating temperature of the extrusion die and extrusion pad is 350°C; the preheating temperature of the extrusion barrel is 400°C; and the extrusion ratio is set to 27.3.

[0040] Example 6

[0041] The difference from Example 5 is that: (1) in step S2, the pressure of the inert gas is adjusted to 3 kPa, and the oxide film of the melt above the furnace is broken; ventilation is continued for 23 minutes; (3) in step S5, the ingot obtained in step S4 is heated and sent to the extrusion barrel of the hot extruder to be extruded into a rod with a specification of φ50 mm; the ingot heating temperature during extrusion is 860°C, and the extrusion speed is 20 mm / s; the preheating temperature of the extrusion die and extrusion pad is 350°C; the preheating temperature of the extrusion barrel is 430°C; and the extrusion ratio is set to 15.76.

[0042] Example 7

[0043] The difference from Example 1 is that: (1) the raw material for producing aluminum bronze QA110-4-4 is put into a 2.5-ton induction furnace for melting, completely melted and the temperature reaches about 1180°C; (2) in step S2, the pressure of the inert gas is adjusted to 4 kPa, and the oxide film of the melt above the furnace is broken; ventilation is continued for 25 minutes; (3) in step S5, the ingot obtained in step S4 is heated and sent to the extrusion barrel of the hot extruder to be extruded into a rod with a specification of φ35 mm; the ingot heating temperature during extrusion is 890°C, and the extrusion speed is 15 mm / s; the extrusion die and extrusion pad are preheated to 400°C; the extrusion barrel is preheated to 440°C; and the extrusion ratio is set to 32.17.

[0044] Example 8

[0045] The difference from Example 1 is that: (1) the raw material for producing aluminum bronze QA110-5-5 is put into a 2.5-ton induction furnace for melting, completely melted and the temperature reaches about 1220°C; (2) in step S2, the pressure of the inert gas is adjusted to 3KPa, and the oxide film of the melt above the furnace is broken; ventilation is continued for 25 minutes; (3) in step S5, the ingot obtained in step S4 is heated and sent to the extrusion barrel of the hot extruder to be extruded into a rod with a specification of φ45mm; during extrusion, the heating temperature of the ingot is 900°C, and the extrusion speed is 12mm / s; the preheating temperature of the extrusion die and extrusion pad is 400°C; the preheating temperature of the extrusion barrel is 450°C; and the extrusion ratio is set to 19.45.

[0046] Example 9

[0047] The difference from Example 8 is that: (1) in step S2, the pressure of the inert gas is adjusted to 3.5 KPa, and the oxide film of the upper melt in the furnace is broken; ventilation is continued for 28 minutes. The ingot obtained in step S4 is heated and sent to the extrusion barrel of the hot extruder, and extruded into a rod with a specification of φ40 mm, and the extrusion ratio is set to 24.63.

[0048] It should be noted that the above method must be used in combination with the capacity of the induction furnace used to adjust the required gas pressure and ventilation time of the melt in the furnace. If the pressure is too low to break the oxide film on the surface of the melt, or the degassing time is insufficient, even if no pores are found in the low magnification of the ingot, after processing, extrusion or drawing, fine loose defects will be found in the flaw detection, which will affect the performance and application of the material.

[0049] Comparative Example 1

[0050] The difference between Comparative Example 1 and Example 3 is that: (1) in step S5, the ingot obtained in step S4 is heated and then fed into the extrusion barrel of a hot extruder to be extruded into a rod with a specification of φ70 mm; the extrusion ratio is set to 8.14.

[0051] Comparative Example 2

[0052] The difference between Comparative Example 2 and Example 1 is that: (1) in step S5, the ingot obtained in step S4 is heated and then fed into the extrusion barrel of a hot extruder to be extruded into a rod with a specification of φ65 mm; the extrusion ratio is set to 9.44.

[0053] Comparative Example 3

[0054] The difference between Comparative Example 3 and Example 8 is that: (1) in step S5, the ingot obtained in step S4 is heated and then fed into the extrusion barrel of a hot extruder to be extruded into a rod with a specification of φ60 mm; the extrusion ratio is set to 11.1.

[0055] Comparative Example 4

[0056] The difference between Comparative Example 4 and Example 4 is that: (1) in step S2, the pressure of the inert gas is adjusted to 1 KPa, and the oxide film of the melt above the furnace is broken; ventilation is continued for 18 minutes; (2) in step S5, the ingot obtained in step S4 is heated and sent to the extrusion barrel of the hot extruder to be extruded into a rod with a specification of φ50 mm; the extrusion ratio is set to 15.76.

[0057] Comparative Example 5

[0058] The difference between Comparative Example 5 and Example 6 is that: (1) in step S2, the pressure of the inert gas is adjusted to 3 kPa, and the oxide film of the melt above the furnace is broken; ventilation is continued for 15 minutes; (2) in step S5, the ingot obtained in step S4 is heated and sent to the extrusion barrel of the hot extruder to be extruded into a rod with a specification of φ38 mm; the extrusion ratio is set to 15.76.

[0059] Comparative Example 6

[0060] The difference between Comparative Example 6 and Example 1 is that: (1) in step S2, the pressure of the inert gas is adjusted to 2.5 KPa, and the oxide film of the melt above the furnace is broken; ventilation is continued for 10 minutes; (3) step S5 is not included.

[0061] Comparative Example 7

[0062] The difference between Comparative Example 7 and Example 1 is that: (1) in step S2, the process of introducing inert gas is not included; (3) step S5 is not included.

[0063] Comparative Example 8

[0064] The difference between Comparative Example 8 and Example 5 is that: (1) in step S2, the process of introducing inert gas is not included; (3) step S5 is not included.

[0065] Comparative Example 9

[0066] The difference between Comparative Example 9 and Example 8 is that: (1) in step S2, the pressure of the inert gas is adjusted to 3 KPa, and the oxide film of the melt above the furnace is broken; ventilation is continued for 10 minutes; (3) step S5 is not included.

[0067] The ingots and bars obtained in Examples 1-9 and Comparative Examples 1-9 were tested, and the results are shown in Table 1 below.

[0068] Table 1 Test results of ingots and bars obtained in Examples 1-9 and Comparative Examples 1-9

[0069] From the comparison between Examples 1-9 and Comparative Examples 1-9 in Table 1, it can be seen that: in a 2.5-ton coreless induction furnace, the above method is used for melt degassing in normal production of aluminum bronze, and the aluminum bronze ingots basically have no porosity defects; combined with the process of adopting a large extrusion ratio when extruding the rods, the flaw detection of the finished rods is all qualified.

[0070] Figure 1 This is a microstructure diagram of the aluminum bronze ingot in Example 3. After low-magnification (a) and high-magnification (b) structure inspection, the internal structure of the material is dense, among which the low-magnification is taken with a mobile phone camera. Figure 2 The microstructure diagram of the aluminum bronze ingot in Comparative Example 6. After low-power (a) and high-power (b) organization inspection, it was found that the organization was loose. It can be seen that the internal organization of the ingot obtained by the process of the present invention is dense. Then the finished aluminum bronze bar was broken, and its end face was visually inspected and high-powered organization was inspected after breaking. Figure 3 This is the high-magnification microstructure test result of the rod produced in Example 3. No defects were found in the ingot after sawing, and the low-magnification test was qualified. No defects were found during the flaw detection of the finished product. After the finished rod was cut, the cross-section was observed to have no defects with the naked eye. The internal structure of the material was dense under high-magnification inspection. Figure 4 The high-magnification microstructure test results of the finished bar produced in Comparative Example 2. No defects were found in the ingot after sawing, and the low-magnification test was qualified; the equipment found defects during the flaw detection of the finished product, and the cross section of the finished bar was not smooth after the end face was cut, and the high-magnification microstructure test found slight loose defects. This shows that the use of a larger extrusion ratio can effectively ensure the density of the bar.

[0071] From the above, it can be seen that when smelting aluminum bronze, the present invention can effectively break the aluminum oxide film on the upper part of the melt by inserting an air pipe or bottom blowing a brick at a suitable pressure and keep it for a certain time, so that hydrogen can float up with the inert gas, and at the same time, the hydrogen in the melt can be effectively removed by combining the oxidation of the melt, thereby reducing the loose defects of the ingot; when processing the rod, the process of large extrusion ratio is adopted, which further improves the density of the finished rod. The preparation method of the present invention is feasible as a preparation of high-density aluminum bronze material.

[0072] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any equivalent changes or modifications made according to the essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for improving the compactness of aluminum bronze extruded rods, characterized in that: It includes the steps of melting, sawing, extruding, trimming, pickling and flaw detection; Among them, the specific method of melting and casting is: (1) Mix the ingredients according to the ratio requirements and put the dried raw materials into an induction furnace to melt them into a melt; (2) When the melt temperature reaches 1140-1260°C, inert gas is introduced into the melt from the bottom of the induction furnace. The pressure of the inert gas should at least be enough to rupture the oxide film on the top of the melt, and the ventilation time should not be less than 20 minutes. (3) Take samples for analysis, adjust the composition, refine, filter, and cast round ingots.

2. A method for improving the compactness of aluminum bronze extruded rods according to claim 1, characterized in that: After the round ingot is sawn into ingots of the length specified by the process, the ingot is heated to 740-900℃ and then sent into the extrusion barrel of the extruder for extrusion to obtain extruded bars of the required specifications; Among them, the preheating temperature of the extrusion die and the extrusion pad is 300-400°C; the preheating temperature of the extrusion barrel is 380-450°C, the extrusion speed is 12-20 mm / s, and the extrusion ratio is ≥15.

3. A method for improving the compactness of aluminum bronze extruded rods according to claim 2, characterized in that: When trimming the extruded rod, cut off 300-500mm of the tail and 100-200mm of the head.

4. A method for improving the compactness of aluminum bronze extruded rods according to claim 1, characterized in that: The aluminum content in aluminum bronze extruded bars is not less than 5%.